Hepatitis B surface antibody (HBsAb) status amongst new applicants of nursing program at International Islamic University Malaysia, Pahang, Malaysia - Jaafar, Khairul Azhar; Zakaria , Rosini (Springer, 2013)
Malaysia started routine Hepatitis B immunization for infants in 1989 using the three-dose regime with the first dose given shortly after birth, thereafter at 1 month and then at 5 months old to coincide with the third dose of DTP/OPV. Anti-HBs immunoglobulin is also given together with the first dose of hepatitis B vaccine (active-passive immunization) at different sites if the mother is found to be a carrier of Hepatitis B virus.